Ensaios sobre ecoeficiência agropecuária no Brasil e na Amazônia Legal - Gama, Thais Gabriela Veras (2022)
Eco-efficiency analysis is a tool that has been increasingly used to measure the relationship between maximizing production and minimizing environmental externalities. In order to investigate the behavior of the agricultural economy and its level of environmental impact in Brazil, the present work is divided into two articles: the first aims to analyze the agricultural eco-efficiency in Brazil, by Federative Unit (FU), from the insertion emissions of carbon dioxide equivalent (CO2e) as an unwanted variable. The methodology applied was the Slacks Based Measura in Data Envelopment Analysis (SBM-DEA) and the Malmquist-Luenberger green productivity index, in the years 2006 and 2017. The data of secondary source was withdrew from the Agricultural Census (IBGE) and the Agricultural Estimation System. Greenhouse Gas Emissions (SEEG V8.0). The main results indicate that FUs in the northern region have lower relative eco-efficiency, and that despite the improvement in green productivity in most Brazilian FUs, it is still possible to reduce the emission of greenhouse gases without compromising agricultural production. The second article aimed to analyze ecoefficiency in the municipalities of the Legal Amazon and identify its possible influencing factors: income, forest cover, educational level and public spending on education, environmental management and agriculture. The methodology used was the DEA-SBM twostage analysis and Tobit regression. Data were obtained through the 2017 Agricultural Census, SEEG V8.0, the System of National Accounts (IBGE), the Accounting and Tax Information System of the Brazilian Public Sector (National Treasury Department), in addition to the Monitoring Project for the Brazilian Public Sector. Deforestation in the Legal Amazon by Satellite (Prodes). The results point to a positive relationship between eco-efficiency and the variables income, educational level and education spending, while the variables of spending on agriculture and environmental management point to a negative influence, the variable of forest cover was not statistically significant.